PERMINTAAN BERAS RUMAHTANGGA PETANI PADI - Harianto Harianto; Dwi Astuti Bertha Susila (Jurnal Agribisnis dan Ekonomi Pertanian, 2009)
The ultimate impact of economic changes, government policies and programs on consumption are determined by responses of households.  The predicted reaction of households to intervention should be a crucial factor in assessing the merits of various policy alternatives.  The results of the present work hopefully enrich our understanding of farm household rice demand behavior.  Rice consumption needs special mention, since the commodity is strategic and is highly preferred in basic diet.The study used AIDS (Almost Ideal Demand System) model to evaluate the rice demand behavior of rice farm households.  In this system approach, econometrics and judgment are employed in obtaining parameter estimates that meet the restriction which, in part, are of a theoretical nature.  Data used in this study was data at household level that has been collected through Patanas (National Farmers Panel).  The estimated results clearly showed that rice demand was price inelastic.  The estimated income elasticity gave significant results statistically.  Income elasticity for rice was also less than unity.  In general, estimated elasticities were quite plausible